Community Resilience of the Sundarbans: Restoring Tourism after Oil Spillage - Hassan, A.; Ramkissoon, Haywantee; Shabnam, S. (2017)
This paper explores the local perspective of community engagement in restoring the natural ecological balance and sustain the eco-tourism opportunities on the backdrop of the recent oil spillage in the Sundarbans. Drawing from community discourse and the community resilience model (Akamani 2012), and national and international media releases in relevance to the oil spillage incident, this study explores community views of the post-Spillage-Sundarbans. A number of suggestions are made for restoring the balance as a platform to build a tourist-friendly resilient community. The study calls for the sustainable public supported community resilience ingenuity. It emphasizes on a harmonised and balanced interrelationship between the private and public parties, stakeholders and beneficiaries to undertake community resilience initiatives for survival.